Ökonomie der Buchindustrie: Literaturbericht - Svenja Hagenhoff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2015)
– This contribution delivers a report on literature relating to economic aspects of the medium of books. Compiling the report proved difficult insofar as the book is or should be the research product of numerous disciplines, such as publishing sciences, management and economics. In the scope of this report, the knowledge gained concerning economic aspects is therefore distributed among many different publication organs which may not seem relevant for the topic at first glance. The literature report includes both academic and practical works and it can be clearly stated that research on economic aspects of the medium of books has led to a considerable amount of significant and useful publications. Statements based on previous findings claiming a lack of theory-based or model-guided research can therefore no longer be maintained. Nevertheless, it must be noted that many contributions are devoted only to particular phenomena, for example influencing factors such as bestsellers or acceptance factors such as ebooks. Larger research areas, such as the structures and functions of the fiction market, which could encompass single items of interest, are a desideratum.
urn:nbn:de:bvb:29-opus4-68261
Keywords: 330; Buchbranche; Buchindustrie; Buchwirtschaft; Buchökonomie; Schriftmedienwirtschaft; Wissenschaftliche Publikation; Medienökonomik; Bibliometrie